Nietzsche on Augustine on Happiness. (May 2017) - Rose, Matthew
This article considers the criticisms made by Friedrich Nietzsche of the ethics of St Augustine. Nietzsche's main criticism presses us to ask whether Augustine can recognize an internal connection between natural human activity and supernatural happiness. The absence of any such connection, alleges Nietzsche, is the self-defeating flaw of Augustine's eudaimonism, a flaw, paradoxically, that only insures human misery. Rebutting these charges, this article argues, requires us to recognize a form of natural happiness that is proportionate to create human nature.